TRANSITIVITY CHOICES AND GENDER REPRESENTATION: A FEMINIST STYLISTIC ANALYSIS OF ALI’S “THE BOOK OF SALADIN” - Asma Iqbal Kayani; Behzad Anwar (Journal of Arts & Social Sciences, 2022)
The present study is aimed to explore how women and men characters are constructed through linguistic choices in Ali’s novel The Book of Saladin (TBOS). Halliday’s (1985) transitivity model as suggested by Mills (1995) in her Feminist Stylistics has been employed for data analysis. To strengthen the analysis, Eggins’ (2004) insights are also given consideration. The data comprises 6 extracts from the novel. A sample size of 107 clauses was drawn to focus on process-participant analysis. The findings indicate that Ali (1998) in TBOS makes a use of all types of processes but with different frequency of occurrences. The women characters are portrayed mainly through Material (41%), Relational (5%) and Behavioral (5%) processes while the men characters are ascribed with more mental (9%) and verbal (4%) processes. These findings indicate that Ali (1998) has represented his women characters more active as compared to his men characters as far as romantic scenes are concerned. The current study confirms Mills (1995) claim that transitivity model is best suited to understand the depiction of gender through linguistic choices.Key Words: Transitivity choices, Feminist Stylistics, Women, Men, Ali, The Book of Saladin (TBOS)